2021
DOI: 10.4102/sajhivmed.v22i1.1196
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of nurse-initiated antiretroviral treatment in South Africa: A narrative review of enablers and barriers

Abstract: Background: The roll out of nurse-initiated and managed antiretroviral treatment (NIMART) was implemented in 2010 by the National Department of Health (NDoH) in South Africa in response to the large numbers of persons living with HIV who needed treatment. To enable access to treatment requires shifting the task from doctors to nurses, which had its own challenges, barriers and enablers.Objectives: The aim of this narrative is to review content on the implementation of NIMART in South Africa over the period 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Tackling knowledge gaps in HIV care amongst nurses may require strong leadership skills that will facilitate the prioritization of continuous professional development and inservice training. Crowley et al (2021), in a narrative review of enablers and barriers of nurseinitiated antiretroviral treatment in South Africa, reported training of nurses as an important enabler [30]. Similarly, Makhado et al (2020) reported continuous education (in-service, refresher, follow-up training) as facilitating HIV guideline adherence by nurses in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Tackling knowledge gaps in HIV care amongst nurses may require strong leadership skills that will facilitate the prioritization of continuous professional development and inservice training. Crowley et al (2021), in a narrative review of enablers and barriers of nurseinitiated antiretroviral treatment in South Africa, reported training of nurses as an important enabler [30]. Similarly, Makhado et al (2020) reported continuous education (in-service, refresher, follow-up training) as facilitating HIV guideline adherence by nurses in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Finally, ensuring the TB program is nurse-led and clinic-based is important for feasibility, cost, and scalability. 14,15 In summary, participants were enthusiastic, but felt the need for more knowledge, clear guidelines, speci c work ows, and continuous momentum. 19 Ensuring the program is patient-centered and aligns with the WHO's End TB Strategy Pillar One, which "puts patients at the heart of service delivery" is also important.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 Finally, ensuring the TB program is nurse-led and clinic-based is important for feasibility, cost, and scalability. 14 , 15 In summary, participants were enthusiastic, but felt the need for more knowledge, clear guidelines, specific workflows, and continuous momentum. Table 4 describes next steps for program implementation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quality improvement strategies such as integrated management of childhood illness (IMCI), 13 practical approach to care kit (PACK) 14 and basic antenatal care (BANC) 15 have all been introduced in PHC. Despite these quality improvement strategies, PHC nurses still report challenges with legislation, policy and guidelines, 12 , 16 inadequate support and mentoring, 16 , 17 non-standardised training and inadequate training and awareness. 13 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%